Moderate Modulation of Cardiac PGC-1α Expression Partially Affects Age-Associated Transcriptional Remodeling of the Heart - Whitehead, Natasha; Gill, Jonathan F.; Brink, Marijke; Handschin, Christoph (Frontiers in Physiology, 2018)
Aging is associated with a decline in cardiac function due to a decreased myocardial reserve. This adverse cardiac remodeling comprises of a variety of changes, including a reduction in mitochondrial function and a decline in the expression of the peroxisome proliferator-activated receptor γ coactivator 1α (PGC-1α), a central regulator of mitochondrial biogenesis and metabolic adaptation in the myocardium. To study the etiological involvement of PGC-1α in cardiac aging, we used mouse models mimicking the modest down- and upregulation of this coactivator in the old and the exercised heart, respectively. Young mice with reduced cardiac expression of PGC-1α recapitulated part of the age-related impairment in mitochondrial gene expression, but otherwise did not aggravate the aging process. Inversely however, moderate overexpression of PGC-1α counteracts numerous key age-related remodeling changes, e.g. by improving blood pressure, age-associated apoptosis and collagen accumulation, as well as in the expression of many, but not all cardiac genes involved in mitochondrial biogenesis, dynamics, metabolism, calcium handling and contractility. Thus, while the reduction of PGC-1α in the heart is insufficient to cause an aging phenotype, moderate overexpression reduces pathological remodeling of older hearts and could thereby contribute to the beneficial effects of exercise on cardiac function in aging.